2012
DOI: 10.2337/dc11-1328
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predictors of Weight Loss and Weight Regain After Intensive Lifestyle Modification, Metformin Treatment, or Standard Care in the Diabetes Prevention Program

Abstract: OBJECTIVEWe tested genetic associations with weight loss and weight regain in the Diabetes Prevention Program, a randomized controlled trial of weight loss–inducing interventions (lifestyle and metformin) versus placebo.RESEARCH DESIGN AND METHODSSixteen obesity-predisposing single nucleotide polymorphisms (SNPs) were tested for association with short-term (baseline to 6 months) and long-term (baseline to 2 years) weight loss and weight regain (6 months to study end).RESULTSIrrespective of treatment, the Ala12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
107
4
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 11 publications
16
107
4
1
Order By: Relevance
“…Interestingly, it has been shown that physical inactivity was associated with a BMI increase (1.95 ± 0.3 kg/m 2 ) in homozygous A-allele carriers compared with homozygous T-allele carriers (Andreasen et al 2008). The FTO genotype has also been shown to interact with weight loss (Delahanty et al 2012), and the A-allele seems to complicate weight maintenance in severe obese patients (Woehning et al 2013). Studies also show that the A-allele is associated with increased energy intake (Speakman et al 2008), but this could not be confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been shown that physical inactivity was associated with a BMI increase (1.95 ± 0.3 kg/m 2 ) in homozygous A-allele carriers compared with homozygous T-allele carriers (Andreasen et al 2008). The FTO genotype has also been shown to interact with weight loss (Delahanty et al 2012), and the A-allele seems to complicate weight maintenance in severe obese patients (Woehning et al 2013). Studies also show that the A-allele is associated with increased energy intake (Speakman et al 2008), but this could not be confirmed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Low-fat diets (Sonestedt et al, 2009) and embarking on a Mediterranean diet (Razquin et al, 2010) may also ' protect against ' FTO -related obesity, and some have suggested that education (Corella et al, 2010) and breast-feeding may also be protective (Dedoussis et al, 2011). There is also evidence that high genetic risk in terms of common variants could mitigate against weight loss via bariatric surgery (Still et al, 2011), caloric restriction (Matsuo et al, 2011), or within a diabetes prevention programme (Delahanty et al, 2012).…”
Section: The Search For ' Obesity Genes 'mentioning
confidence: 99%
“…In addition, 49 loci associated with body fat distribution (waist-to-hip ratio adjusted for BMI) were identified [3] . The first evidence for a role of genetic predisposition in weight loss and weight regain came from a study by Delahanty et al [4] , which showed that several gene variants were associated with short-and long-term weight loss and weight regain. Based on a meta-analysis of available studies, Xiang et al [5] concluded that individuals carrying the homozygous fat mass and obesity-associated (FTO) obesity-predisposing allele lose more weight by means of diet or lifestyle interventions than noncarriers.…”
Section: Introductionmentioning
confidence: 99%